The European Central Bank as lender of last resort - Gerhard Illing; Philipp Johann König (DIW Economic Bulletin, 2014)
In the wake of the recent European debt crisis, the European Central Bank (ECB) has grown significantly in importance. As the crisis worsened, the ECB needed to take measures that went far beyond standard monetary policy operations - particularly with respect to its function as lender of last resort. It provided the banking sector with almost unlimited liquidity and, in addition, purchased government bonds of distressed countries outright. Eventually, in the summer of 2012, it followed through on its promise to do everything possible to save the euro as a common currency. This announcement temporarily stabilized financial markets and the countries in crisis. Nevertheless, compared to other central banks, the ECB is inhibited in its scope of activities: unlike, for example, the US Federal Reserve (Fed), the European Central Bank has no well-defined institutionally anchored fiscal backing. Consequently, the measures it can take are limited by the maximum loss it can incur. This also means that the ECB must protect itself more than other central banks against financial risks from its monetary policy operations. In particular, during a crisis, this restricts its scope for taking measures to fulfill its mandate - securing price stability. Moreover, the ECB has taken on the role of lender of last resort for euro area governments with its announcement in the fall of 2012 to purchase government bonds of distressed countries in the euro area, if necessary, and under strict conditions. It felt forced to do so because the euro area did not have a fiscal institution capable of stopping the crisis worsening and preventing a break-up of the European Monetary Union. At the same time, however, it is indeed questionable whether such activities are included in the ECB's mandate. The European Stability Mechanism (ESM) would, in principle, be better suited to act as a lender of last resort for governments should future crises occur. However, it should be given access to ECB credit facilities in order to fully perform this function.
Keywords: E52; E58; G21; F36; 330; Central Banking; Lender of Last Resort; Monetary Policy; EuropeanMonetary Union; Banking Crises